SUSTAINABLE DEVELOPMENT OF AGRICULTURE IN UZBEKISTAN BASED ON A GREEN ECONOMY - Bobojonova Madina Jumaniyoz qizi (American Journals, 2024)
Currently, various measures are being considered for the development of the green economy. We can take the agricultural sector as an example. In this regard, projects produced in the green economy are leading in Uzbekistan as well. In the article, the principles of green economy are mentioned about ways to ensure sustainable development in agriculture, the measures implemented in agriculture to solve environmental problems. Environmentally friendly technologies and innovations increase the efficient use of resources in agriculture and improve the well-being of rural residents. It was talked about strengthening the agricultural sector by introducing the principles of green economy in Uzbekistan and improving the quality of environmentally friendly technologies and their application by studying international experiences. In this regard, the creation of an effective system that helps to attract private investments for the modernization, diversification and sustainable development of the agriculture and food chain is considered as the main goal of this priority direction.
Keywords: Green economy, innovation effect, technological leadership transfer effect, transmission, environmentally friendly technologies, cluster, AKIS, resource, economic growth.